Front-Matter - Windia, Wayan P (Udayana Journal of Law and Culture, 2019)
The current edition contains articles that represent the “The Dynamics of Global Society”. It is generally understood that the current global society comprises ‘traditional’ actors such as States and International Organizations and other emerging actors that may play a key role in global interactions. The first article tries to advance the issue of diaspora that faced by almost all countries in the world due to the freedom of movement of persons by taking an example of Indonesian Diaspora. The idea of developing a new diaspora category, called as a “special friends of Indonesia’ (Indonesianist), seems not supported by the current law and regulation. Whatsoever, in a view of that this category would conceptually not become a utopia, this article argues that student mobility programs may be a means of nurturing of future Indonesianist. The second and third articles reveal global economic competitions, as a reality of the global society dynamics,  that have an impact in the field of both private and public laws. The second article analyzes the differences in legislation of vertical restraints in the European Union (EU) and the United States (US). It offers a relatively balanced perspective by assessing that exclusive distribution and non-compete clauses may have both positive and negative effects on international markets.  The example of competition law in the EU has also been addressed in the third article which discusses the approach used in ASEAN single aviation market competition laws. On one hand, this article moderately acknowledges regional enforcement as a means of preventing and opposing unfair competition, but on the other hand, it also proposes the adoption of the concept of international comity as an achievable alternative to existing ASEAN competition laws. The fourth article supports the right of Faroese indigenous peoples in continuing their whaling tradition that re-contextualize the cultural behavior of actors in international law. As it is generally known, the global society is quite diametrically separated between those who consider that such whaling activities are understandable in the context of research and tradition and those who strongly advocate the termination of whaling as represented by environment and nature non-governmental organizations. The topic presented in the last article may not genuinely link to the meaning of a global society as it discusses the financial policy which was taken in responding to the natural disaster. There may be a little connection, in which the economic problems faced by local residents of Karangasem Regency in Bali, especially those who work in the tourism industry, occurred because of the decreasing number of foreign tourist visits. This article also establishes an argument that the social and cultural life of the local society should be taken into account when relevant authorities adopt a financial policy. I would like to express my gratitude to all authors, editors, and reviewers from many countries for their valuable contribution to the present edition. I do believe that there will be more high-quality papers to be submitted to, and publish by, UJLC for the next editions. Editor in Chief